LITERATURE REVIEW: DEVELOPMENT OF GAMIFICATION LEARNING MEDIA IN CHEMISTRY - Yulian, Satifa Ananda; Rengganis, Ajeng Ayu; Hazlina, Nur; Siburian, Putri Dela; Kadir, Nurdianah Abdul; Rahmadani, Agung (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Science and technology evolved with the times and has very important influence in various aspects of life, one of them is the aspect in education. Utilization of science and technology in education can be applied through innovation in developing learning media. Gamification-based learning media is a game designed as a learning instrument. Gamification is one of the learning media innovations that can be utilized in chemistry learning for increase motivation and student learning outcomes. The writing of this literature review purposed for examining the development of gamification learning media in chemistry learning. The method used in this literature review is narrative literature review by collecting data of article related to gamification learning media that published within a period 2014-2023. Data analysis is carried using an simplified approach. The articles used in this literature review were 51 articles from accredited national and international journals obtained from Google Scholar. Based on the result of the literature review, it was found that gamification learning media can increase student motivation in chemistry learning. Gamification can also motivate teacher to innovate in creating learning media that can interest student. Therefore, gamification can be a new trend in chemistry learning. Keywords: gamification; chemistry learning media; education game